Depositional systems of the late Eocene Yolomécatl Formation, northwestern Oaxaca, southeastern Mexico: a first approach - Ismael Ferrusquía-Villafranca; José Ramón Torres-Hernández; José E. Ruiz-González; Enrique Martínez-Hernández (Revista Mexicana de Ciencias Geológicas)
The discrimination/characterization of depositional systems recorded in formal lithostratigraphic, Cenozoic, continental, epiclastic units of Mexico, is largely a pending task, notwithstanding its great academic and economic importance. Contributing to fill this gap, we present a first approach to discriminate and characterize the depositional systems of the late Eocene Yolomécatl Formation, which fills the namesake, triangle-shaped tectonic basin, and carries the southernmost Paleogene vertebrate fauna of North America. The study area lies between 17°25’–17°30’ North Latitude and 97°29’–97°36’ West Longitude, and between 2000–2500 m a.s.l.; the federal highway 125 traverses it; Santiago Yolomécatl is the main town.